AB1030 Febuxostat versus allopurinol streamlined trial (FAST): baseline characteristics of the randomised patient population. (12th June 2018) - Mackenzie, I.; MacDonald, T.; Ford, I.; Nuki, G.; ,
Abstract : Background: The Febuxostat versus Allopurinol Streamlined Trial (FAST) is a prospective, randomised, open-label, blinded endpoint trial comparing the cardiovascular safety of allopurinol and febuxostat in patients with symptomatic hyperuricaemia. 1 The trial includes patients aged over 60 years who are taking chronic allopurinol therapy at baseline and have at least one additional cardiovascular risk factor. After uptitration on allopurinol to reach EULAR urate targets, patients are randomised to febuxostat or allopurinol then followed up for events. Patient recruitment to the trial completed in late 2017 and follow-up is ongoing. Objectives: To describe the baseline characteristics of the patients randomised into the FAST study. Methods: The primary endpoint of the FAST study is the composite of non-fatal myocardial infarction, non-fatal stroke or cardiovascular death. The primary analysis is a non-inferiority analysis with a non-inferiority upper limit for the hazard ratio for the primary outcome of 1.3. Results: 6142 patients from UK, Denmark and Sweden have been randomised into the FAST study. The mean age at randomisation was 71.0±6.4 (SD) years. 85.3% of participants are male. 57.3% are former smokers and 7.9% current smokers. Mean systolic blood pressure was 138±18 mmHg and mean diastolic blood pressure 75±12 mmHg. Mean body mass index was 31.1±5.2 kg/m 2 . 10.7% of participants had a history of previous myocardial infarction, 5.0% a history of previous cerebrovascular accident and 4.8% a history of peripheral arterial disease. 22.5% had a history of diabetes mellitus and 4.6% a history of heart failure. 78.0% had a history of high blood pressure. 33.3% had a history of any cardiovascular disease (defined as history of myocardial infarction, cerebrovascular accident, transient ischaemic attack, acute coronary syndrome, coronary revascularisation, angina pectoris or heart failure). The mean baseline urate at study entry (screening) was 297±47 umol/L. The mean allopurinol dose being taken at study entry (screening) was 225±106 mg daily. 2206 patients (35.9%) had at least one uptitration of allopurinol dose prior to randomisation. Conclusions: This ongoing European trial will report on the cardiovascular safety of febuxostat versus allopurinol in patients with symptomatic hyperuricaemia. Reference: [1] MacDonald TM, Ford I, Nuki G, Mackenzie IS, et al. Protocol of the Febuxostat versus Allopurinol Streamlined Trial (FAST): a large, prospective, randomised, open, blinded-endpoint study comparing the cardiovascular safety of allopurinol and febuxostat in the management of symptomatic hyperuricaemia. BMJ Open2014;4:e005354. doi:10.1136/bmjopen-2014-005354 Acknowledgements: The FAST study is funded by Menarini and sponsored by the University of Dundee. Disclosure of Interest: None declared